The outcome of staghorn calculi treated in HUSM - Kamarulzaman, Mohd Nazli; Rahman, Mohd Nor Gohar; Mahmood, Zainal; S, Syed Hassan; MD, Mohd Ashraf (Universiti Sains Malaysia, 2005)
Urinary stone is a common problem encountered in clinical practice in Kelantan. In previous study by Noori et al, he found that 90% of patients with urinary tract stone disease presented with some degree of renal impairment and 70% of them further deteriorated post treatment.